Challenges and Success Factors in Digital Classroom Implementation: Tantangan dan Faktor Keberhasilan dalam Implementasi Kelas Digital - Fairus Ad Dailamay Wartindya Pradana Saputra; Erna Yayuk; Agus Tinus (Universitas Muhammadiyah Sidoarjo, 2025)
Digital transformation in education has gained momentum, prompting schools to adopt innovative strategies to enhance learning. Specifically, the Digital Classroom program has emerged as a strategic initiative to integrate technology into teaching at the junior high school level. However, limited empirical studies address the comprehensive implementation framework of such programs, including planning, execution, and evaluation phases, along with influencing factors. This study aims to analyze the implementation of the Digital Classroom program by focusing on four dimensions: planning, implementation, evaluation, and the identification of supporting and inhibiting factors. The results reveal that structured planning, including curriculum design and staff training, enables a smoother transition, while challenges persist in infrastructure readiness and teacher digital literacy. The novelty lies in its detailed mapping of multistakeholder evaluation mechanisms and the interplay between technical readiness and human adaptability. These findings imply that sustained professional development, infrastructure investment, and collaborative governance are critical to optimizing digital learning environments in secondary education. Highlights: Structured Implementation: The program was carefully planned through needs analysis, digital curriculum design, and staff training. Monitoring and Evaluation: Regular assessments by schools, foundations, and local offices help measure the program’s impact on learning outcomes. Key Challenges & Support: While leadership and device availability support success, internet limitations and teacher resistance remain barriers. Keywords: Digital Classroom, Program Implementation, Educational Innovation, School Digitalization, Technology in Education.